Wearability testing of ambulatory vital sign monitoring devices: a prospective observational cohort study - Areia, C; Young, L; Vollam, S; Ede, J; Santos, M; Tarassenko, L; Watkinson, P (JMIR Publications, 2020)
Background: Timely recognition of patient deterioration remains challenging. Ambulatory monitoring systems (AMSs) may provide support to current monitoring practices; however, they need to be thoroughly tested before implementation in the clinical environment for early detection of deterioration.